Identification of Conserved and Divergent Strigolactone Receptors in Sugarcane Reveals a Key Residue Crucial for Plant Branching Control - Hu, Anqi; Zhao, Qiaoqiao; Chen, Li; Zhao, Jinping; Wang, Yuehua; Feng, Kuiliang; Wu, Ling; Xie, Miao; Zhou, Xuemei; Xiao, Langtao; Ming, Zhenhua; Zhang, Meng; et al. (Frontiers in Plant Science, 2021)
Strigolactones (SL) are a class of important plant hormones mainly regulating plant architecture such as branching, which is crucial for crop yield. It is valuable to study SL signaling pathway and its physiological function in sugarcane, the most important sugar crop, for further molecular breeding. Here, two putative SL receptors, SsD14a/b and the interacting F-box protein, SsMAX2, were identified in Saccharum spontaneum. SL induces both SsD14a and SsD14b to bind with SsMAX2 in yeast. But SsD14b could not bind with either AtMAX2 or AtSMXL7 while SsD14a could. Overexpression of SsD14a or SsMAX2 rescued the increased branching phenotypes of Arabidopsis thaliana d14-1 and max2-3 mutants, respectively. Moreover, the crystal structure of N-terminal truncated SsD14a was solved, with an overall structure identical to AtD14 and OsD14 in the open state, consistent with its conserved activity in Arabidopsis. Consistent with the biochemical observations, SsD14b could not completely complement in d14-1 although these two SsD14 proteins have almost identical primary sequences except for very few residues. Complement with SsD14b and SsMAX2 simultaneously also failed to rescue the multi-branching phenotype thoroughly, indicating D14-MAX2 complex alone is not sufficient for regulating branching. Subsequently, we found that residue R310 at α10 helix of SsD14a is crucial for the binding with SsSMXL7/AtSMXL7 but not SsMAX2. Thus, the site-equivalent single residue P304R substitution of SsD14b was designed. The transgenic lines containing SsD14bP304R was exactly the same with Col-0 in branching phenotype. These results suggested that the recovered binding capacity of SsD14b with SsSMXL7/AtSMXL7 was essential for regulating branching. Moreover, this conserved Arg residue across species defines the activity of SL receptor at its specific interaction with SMXL repressors. Taken together, our work reveals a conserved core SL signaling pathway in sugarcane and opens up new horizons in the use of natural variants from various species.